A prospective study on evaluation of Mannheim peritonitis index in cases of spontaneous hollow viscus perforation at a tertiary health care center - Ramrao, Gangasagare Manoj; Pawara, Avinash; Mujawar, Parvez (International Journal of Research in Medical Sciences, 2025)
Background: Spontaneous hollow viscus perforation leading to peritonitis remains a significant surgical emergency with high mortality despite advances in medical care. The Mannheim Peritonitis Index (MPI) is a prognostic scoring system designed to assess disease severity and predict outcomes. This study aimed to evaluate the prognostic value of MPI in predicting mortality and morbidity in patients with spontaneous hollow viscus perforation. Methods: A prospective observational cross-sectional study was conducted at a tertiary care center in Maharashtra, India, over 18 months (April 2023 to August 2025). Ninety-seven patients with spontaneous hollow viscus perforation were enrolled. MPI scores were calculated for each patient based on eight risk factors including age, gender, organ failure, malignancy, preoperative duration, origin of sepsis, type of peritonitis, and exudate characteristics. Statistical analysis was performed using Chi-square test, Fisher's exact test, and Pearson correlation coefficient. Results: The overall mortality rate was 11.3% (11/97). Patients with MPI score >26 showed significantly higher mortality (9/41, 21.9%) compared to those with MPI ≤26 (2/56, 3.6%) (p=0.00). Significant mortality predictors included age >50 years (p=0.01), presence of malignancy (p=0.02), organ failure (p=0.00), preoperative duration >24 hours (p=0.04), and purulent/fecal exudate (p=0.03). MPI showed positive correlation with hospital stay (r=0.463, p=0.01) and mortality (r=0.429, p=0.00). Patients with MPI >26 had prolonged hospitalization (85.4% stayed >15 days. Conclusions: MPI is a reliable, simple, and effective prognostic tool for risk stratification in patients with spontaneous hollow viscus perforation. It accurately predicts mortality and hospital stay duration, enabling early identification of high-risk patients who require aggressive management and intensive care support.